الأسس اللامادية في تصميم المشافي" - محمد جلال استانبولي (Tishreen University, 2019)
إن المهمة الأساس للنظام الصحي المساعدة على تحسين الحالة الصحية للناس, ومن الضروري الأخذ في الاعتبار الثورة العميقة في علم دراسة الأمراض وتطور مفهوم الصحة, التي احدثت تغييراً كبيراً في المجال التكنولوجي وتطور صورة شبكة الخدمات, وظهور مفهوم الطب الإذاعي والمساعدة البيتية عن طريق الانترنيت. أضف إلى ذلك رغبة المرضى بان يصبح العلاج اقل معاناة. وقد أدى ذلك كله إلى تغيرات عديدة في مفاهيم التصميم في المشافي الحديثة. ودعا إلى ضرورة إعادة النظر في الأسس التصميمية لمباني الصحة العامة في قطرنا والتي اعتمدت فقط على تامين الاسس المادية. ان من مهام المصمم لمباني المشافي الحديثة أن يعي بأن المبنى يجمع في ذاته مفاهيم وفعاليات متعددة, فقد تحول من مفهوم علاج المرضى إلى التركيز  على إنسانية المرضى. والاهتمام بالإجراءات كلها سواء في عملية المعالجة وعملية الرعاية الصحية وبأن هناك العوامل الأخرى اللامادية التي يجب أخذها بالاعتبار في أثناء عملية تصميم. The main task of the health care system is to help the improvement of the health level of people. It is necessary to keep in mind the deep revolution in the study of diseases and the development of the concept of health, which followed an unusual change in the technology area and the development of on-line medical services, and the emergence of the concept of radio medicine and homework assistance via the Internet, in addition to answering to the patient's desire of making treatment less painful. All this has led to many changes in the concepts of design in modern hospitals. So it is necessary to reconsider the principles of design of public healthcare buildings which often adopted the basic requirements. It is the architect's responsibility to recognize in his/her design of modern hospitals that the building hosts multi-events. There is a shift from the concept of patient treatment to focus on the humanity of patients, and interest in all parts, both in the process of treatment as well as healthcare and that there are immaterial factors that should be taken into consideration during the design process.